Meaning of Mentoring in the Professional Activities of Newly Qualified Music Teachers - Bušmaitė, Eglė; Kavaliauskienė, Angelė (Jaunųjų mokslininkų darbai, 2021)
Newly qualified music teachers, when they start their professional career, face challenges and need help from experienced teachers, mentors. Mentoring is defined as collaboration based on a pre-arranged plan that meets personal development needs. The process involves experiential learning in shaping the mentee’s attitude towards pedagogical work, responsibilities and duties. The mentor’s activities are very diverse, so he/she needs to possess a wide range of competences, knowledge, 7 values, personal qualities and abilities. The mentor’s competences are based not only on professional, pedagogical, personal, but also on management, adult education, counselling and administrative skills.The aim of this qualitative research was to identify challenges and difficulties newly qualified music teachers face and measures that would help them integrate into the professional labour market. Scientific and methodological literature was analysed and a standardised open-ended interview with 8 newly qualified music teachers was carried out in April, 2020.This qualitative research revealed that the majority of newly qualified music teachers face challenges during the adaptation period. An assigned experienced teacher, a mentor, can help a newly qualified teacher overcome professional challenges: a lack of a teaching experience and of classroom management skills, unfriendly attitudes of fellow teachers, negative emotions. A newly qualified music teacher needs assistance in three areas: professional (pedagogy and subject teaching), getting to know students, active engagement in school activities. Willingness to communicate and cooperate, an ability to motivate, a positive outlook, commitment and reliability are the mentor’s characteristics that positively affect career success of a newly qualified music teacher.
Keywords: mentoring; mentor’s activities and competences; newly qualified music teachers